The Nature and Transformation of Corporate Headquarters: A Review of Recent Literature and a Research Agenda - Pettigrew, A; Ferlie, E (1996)
In this paper we suggest that the study of attempts to secure headquarters level change may now be of increasing significance. Evidence of a wave of HQ level change is beginning to accumulate and requires further investigation. The twin purposes of this paper are: (1) in descriptive terms, to gather such evidence as is already available about the nature and extent of HQ level change; to assess the strengths and weaknesses of the extant literature; to suggest where further descriptive work needs to take place; and (2) in explanatory terms, to build some initial and alternative organizational and managerial theories that could inform the study of HQ change; to propose a medium-term research agenda that can be tested in the field.